Enhancement of solubilization and biodegradation of petroleum by biosurfactant from Rhodococcus erythropolis HX-2. Issue 2 (7th February 2020) - Hu, Xin; Qiao, Yue; Chen, Long-Qiang; Du, Jian-Fei; Fu, Yue-Yue; Wu, Si; Huang, Lei
Abstract: The demand to repair areas contaminated with hydrocarbon products has led to the development of new technologies for the treatment of contaminants in an unconventional method, that is, no physical or chemical methods are used. Biosurfactants are amphiphilic biomolecules produced by microorganisms that can be used in environments contaminated by petroleum products due to their unexceptionable tensile properties. Petroleum degrading strain Rhodococcus erythropolis HX-2 was found to be an effective producer of biosurfactants. The resulting biosurfactant (named NK) exhibits high physicochemical properties in terms of surface activity. It is capable of reducing surface tension from 54.99 to 28.89 mN/m and critical micelle concentration (CMC) is 100 mg/L. NK was found to be a substitute for chemically synthesized surfactants because of its higher solubilization efficiency for petroleum and polycyclic aromatic hydrocarbons, superior to SDS, Tween 80, Triton X-100 and Rhamnolipid (a wide used biosurfactant). In addition, it exhibits favorable emulsion stability over a wide range of pH (3–10), temperature (20–100 °C) and salinity ranges (5–20 g/L). It was found that the addition of biosurfactant can improve the efficiency of petroleum degradation, therefore it has potential applications in bioremediation. Highlights: Rhodococcus erythropolis HX-2 is an effective petroleum degrading strain. HX-2 is a potential source of biosurfactant production. The biosurfactant NK reduces surface tension and exhibits high emulsification activity. The biosurfactant NK is effective over a wide range of temperatures, pH and salinity. The biosurfactant NK shows high solubilization efficiency for petroleum as well as polycyclic aromatic hydrocarbons.